2016
DOI: 10.3109/10826084.2015.1090452
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Intervening to Prevent Driving While Intoxicated: The Problem of Driving While Intoxicated (DWI)

Abstract: Background Driving while intoxicated (DWI) is a significant public health issue. The likelihood someone will intervene to prevent driving while intoxicated is affected by the characteristics of the individuals and the context of the potential driving scenario. Understanding such contexts may help tailor public health messages to promote intervening from those who are nearby to an intoxicated driver. Objective This systematic review investigates the behavior of those close to an intoxicated driver and factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…Since those campaigns' inception in 1982, two-thirds of Americans have tried to prevent someone from driving after drinking, and traffic deaths involving alcoholimpaired crashes have decreased 65%. 55,56 The comparable lethal means safety enterprise would encourage friends and family to talk with those in crisis about storing firearms safely. The campaign must use spokespersons who have strong respect and credibility among firearm owners, such as the NSSF and the United States Concealed Carry Association who have developed firearm suicide prevention websites and videos.…”
Section: Recommended Actions To Further Promote Safe Storage Develop mentioning
confidence: 99%
“…Since those campaigns' inception in 1982, two-thirds of Americans have tried to prevent someone from driving after drinking, and traffic deaths involving alcoholimpaired crashes have decreased 65%. 55,56 The comparable lethal means safety enterprise would encourage friends and family to talk with those in crisis about storing firearms safely. The campaign must use spokespersons who have strong respect and credibility among firearm owners, such as the NSSF and the United States Concealed Carry Association who have developed firearm suicide prevention websites and videos.…”
Section: Recommended Actions To Further Promote Safe Storage Develop mentioning
confidence: 99%
“…In addition, we observed that no participants believed that they could be punished if they were assessed on BAC by a police officer, which also occurs in developed countries (21) . Nygaard et al (22) evaluated the motivations to drive after drinking alcohol in adolescents who admitted to the behavior of drinking and driving and/or had already suffered a car accident after drinking and concluded that an awareness of the lack of systematic surveillance and disregard for the law influenced their decision to drive after drinking.…”
Section: Discussionmentioning
confidence: 86%
“…The decision to take action is explained by the five steps of the bystander or social intervention model [48]. At first, a potential intervener should notice the event, subsequently take it seriously and feel responsibility to intervene, and lastly should know what to do and decide to take action [49]. Besides the bystander effect, a dependency position relative to the colleague in question might affect a physician's willingness to act [50].…”
Section: Plos Onementioning
confidence: 99%